Manajemen Strategi Dalam Produksi Dokumenter Televisi “Titisan Nusantara” Edisi “ Jejak Warisan Budaya Sebatang Klembak Menyan” - Syakira, Luthfiah; Giantoro, Edi (Yayasan Tri Edukasi Ilmiah, 2024)
Managing a production team in creating a television program requires a strategy to get the process and results according to plan. The thesis on the creation of the production work of Strategic Management in the Production of the Television Documentary